Environmental and technological factor diffusion with innovation and firm performance: Empirical evidence from manufacturing SMEs - Akbar, Ahsan; Hussain, Arsalan; Shahzad, Arfan; Mohelska, Hana; Hassan, Rohail (Frontiers in Environmental Science, 2022)
The adoption of e-commerce is essential in today’s dynamic business environment to optimize the overall firm performance of manufacturing SMEs. This research investigates the influence of environmental and technological factors to promote e-commerce adoption and subsequent firm performance in manufacturing SMEs. Technology usage for sustainable production is becoming a global phenomenon, though it seems less prevalent in emerging economies. Fewer studies address technology adoption issues to enhance corporate performance in Pakistani manufacturing SMEs. The present study opted a resource-based view with the diffusion of innovation theory to formulate a research framework. We chose a stratified proportionate random sampling method to collect data by selecting four heterogeneous strata. Out of 800 distributed questionnaires, 368 top and middle-level managers of textile, leather, sports, and surgical SMEs of Pakistan returned the questionnaire. This study employed PLS-SEM for empirical analysis. The results showed that both the technological factors relative advantage and technology readiness has a significant positive relationship with the Use of e-commerce. However, environmental factors i.e., competitive pressure has an insignificant affect on e-commerce usage. Nevertheless, the government support has a significant positive effect on e-commerce usage in SMEs. Overall, e-commerce adoption depicts a positive association with firm performance.